1986
DOI: 10.1084/jem.163.5.1113
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-independent killing by alveolar macrophages.

Abstract: Alveolar macrophages play a key role in defense of the host against pulmonary infection (1-6). Their clinical importance is emphasized by the high incidence of life-threatening pneumonia (7,8) in patients with abnormal macrophage function (6) or impaired ceU-mediated immunity (6-9). However, the mechanisms by which alveolar macrophages kill microorganisms are poorly understood.We recently examined the mechanism by which human alveolar macrophages kill the intracellular parasite, Toxoplasma gondii (10). We chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Normal rat and human alveolar macrophages, however, kill intracellular toxoplasma by a mechanism that does not involve toxic oxygen metabolites but probably involves phagosome formation. This antimicrobial mechanism is not present in resident murine alveolar and peritoneal macrophages [3]. There is a large body of data suggesting that oxygen-independent mechanisms of intraceUular killing by phagocytic cells are impor-tant.…”
Section: Discussionmentioning
confidence: 98%
“…Normal rat and human alveolar macrophages, however, kill intracellular toxoplasma by a mechanism that does not involve toxic oxygen metabolites but probably involves phagosome formation. This antimicrobial mechanism is not present in resident murine alveolar and peritoneal macrophages [3]. There is a large body of data suggesting that oxygen-independent mechanisms of intraceUular killing by phagocytic cells are impor-tant.…”
Section: Discussionmentioning
confidence: 98%
“…Scavengers of oxygen intermediates (Catterall, Sharma & Remington, 1986) were obtained from Sigma GmbH, Deisenhofen, West Germany, and used at the concentrations shown. Superoxide dismutase, 3000 U/mg (2-5 mg/ml) was used for superoxide anion; catalase from bovine liver recrystallized twice (2-5 mg/ml) for hydrogen peroxide; and histidinc (10 mM) and diazabicyclooctane (1 ITLM) for singlet oxygen radicals.…”
Section: Scavengers Of Oxygen Intermediatesmentioning
confidence: 99%
“…46,47 Macrophages (human and rat alveolar and peritoneal) possess oxygen-dependent and oxygen-independent anti-microbial activities, both of which are active in unstimulated and activated cells. Studies by Catterall and others 48,49 and Chang and Pechere 50 demonstrated that intracellular killing of T. gondii by human and rat alveolar and peritoneal macrophages was by a non-oxidative mechanism, with no oxidative burst being triggered in these cells. Catteral and others 48 also investigated the roles of oxygen scavengers and found that these metabolites had no effect on the toxoplasmicidal activities of human and rat macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Catterall and others 48,49 and Chang and Pechere 50 demonstrated that intracellular killing of T. gondii by human and rat alveolar and peritoneal macrophages was by a non-oxidative mechanism, with no oxidative burst being triggered in these cells. Catteral and others 48 also investigated the roles of oxygen scavengers and found that these metabolites had no effect on the toxoplasmicidal activities of human and rat macrophages. This suggests that the intracellular killing of T. gondii in these cells does not involve toxic oxygen metabolites.…”
Section: Discussionmentioning
confidence: 99%